Cassava Breeding Trials - Edaphoclimatic Zone 7: Semi-Arid - International Center for Tropical Agriculture (2015)
Cassava germplasm development at CIAT is centered on the development of improved gene pools for specific edapho-climatic zones with importance for cassava production. The most relevant ecosystems are the semi-and and sub-humid tropics, for which the majority of efforts are devoted. The main selection activity is conducted in sites selected to represent the conditions of the target ecosystem. For each zone, a recurrent selection program with a progressive set of stages is followed. As the stages progress more emphasis is given to traits of lower heritability, because more planting material for each genotype is available and the evaluation can be conducted in bigger plots with replications. Certain selection criteria are of general Importance across ecosystems (i.e. yield potential, dry matter content), while others are specific for each ecosystem (i e. specific pests and/or diseases). This dataset provides CIAT cassava breeding trial data for activities conducted in the Semi-arid zone